The Belzec death camp : history, biographies, remembrance - Webb, Chris, 1954- (Ibidem-Verlag, 2016)
This book is a comprehensive account of the Belzec death camp in Poland, which was the first death camp to use static gas chambers as part of the Aktion Reinhardt mass murder program. It covers the construction and the development of the mechanisms of mass murder. The story is painstakingly told from all sides-the Jewish inmates, the perpetrators, and the Polish inhabitants of the village of Belzec, who lived near the factory of death. A major part of this work is the Jewish Roll of Remembrance, which covers the few survivors and the lives of some of the Jews among the many hundreds of thousands who perished in Belzec. The book is richly illustrated with historical and modern photographs, some of which are previously unpublished, as well as documents and drawings.